Grammatical Role Parallelism Influences Ambiguous Pronoun Resolution in German - Sauermann, Antje; Gagarina, Natalia (Frontiers in Psychology, 2017)
Previous research on pronoun resolution in German revealed that personal pronouns in German tend to refer to the subject or topic antecedents, however these results are based on studies involving subject personal pronouns. We report a visual world eye-tracking study that investigated the impact of the word order and grammatical role parallelism on the online comprehension of pronouns in German-speaking adults. Word order of the antecedents and parallelism by the grammatical role of the anaphor was modified in the study. The results show that parallelism of the grammatical role had an early and strong effect on the processing of the pronoun, with subject anaphors being resolved to subject antecedents and object anaphors to object antecedents, regardless of the word order (information status) of the antecedents. Our results demonstrated that personal pronouns may not in general be associated with the subject or topic of a sentence but that their resolution is modulated by additional factors such as the grammatical role. Further studies are required to investigate whether parallelism also affects offline antecedent choices.